2018
DOI: 10.1016/j.metabol.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide has a pronounced effect on energy intake but not energy expenditure in non-diabetic subjects with obesity: A randomized, double-blind, placebo-controlled trial

Abstract: Compared with placebo, exenatide decreased early ad libitum energy intake but did not change 24 h-EE. However, the reduction was more modest in relative versus absolute terms (i.e. below that needed for WMEN). Thus, although rate of weight change was greater in the exenatide treated subjects at 5 weeks, the absolute difference in weight was not significant. These findings indicate that although exenatide reduces food intake, it may be more beneficial in blunting overeating and thus may serve to more prevent we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…The impressive weight loss observed with several peptides in mice often reflects contributions from sympathetic nervous system engagement, BAT activation, and induction of energy expenditure, metabolic events that have rarely been recapitulated in sustained human studies. For example, GLP-1 increases sympathetic nervous system activity [ 115 ] and energy expenditure in animal experiments [ 116 , 117 ], but not in humans with T2D or obesity [ [118] , [119] , [120] , [121] , [122] ]. Similar findings relate to glucagon-containing agonists that robustly activate BAT and energy expenditure in mice [ 46 , 48 , 50 ], yet these mechanisms have not made appreciable contributions to weight loss in human studies.…”
Section: Pitfalls and Data Limitationsmentioning
confidence: 99%
“…The impressive weight loss observed with several peptides in mice often reflects contributions from sympathetic nervous system engagement, BAT activation, and induction of energy expenditure, metabolic events that have rarely been recapitulated in sustained human studies. For example, GLP-1 increases sympathetic nervous system activity [ 115 ] and energy expenditure in animal experiments [ 116 , 117 ], but not in humans with T2D or obesity [ [118] , [119] , [120] , [121] , [122] ]. Similar findings relate to glucagon-containing agonists that robustly activate BAT and energy expenditure in mice [ 46 , 48 , 50 ], yet these mechanisms have not made appreciable contributions to weight loss in human studies.…”
Section: Pitfalls and Data Limitationsmentioning
confidence: 99%
“…related to albumin's ability to binds a host of substances including hormones known to alter appetite (e.g. thyroxine, glucocorticoids) (31)(32)(33). Albumin may serves as a carrierligand for these substances providing transport to sites of action, metabolism, and excretion (34).…”
Section: A B D Cmentioning
confidence: 99%
“…Previous studies have demonstrated an effect of GLP-1 receptor agonists on energy intake [10,20] through both central and peripheral mechanisms in rats and humans [21,22]. Our findings that GLP-1 was negatively associated with carbohydrate and LF/HSS intake and not total energy intake indicates a possible different mechanism by which GLP-1 regulates intake and may be explained by the potential role of GLP-1 in food reward and satiety.…”
Section: Discussionmentioning
confidence: 54%